Manajemen strategis pada lembaga pendidikan islam dalam menghadapi tantangan Kurikulum Merdeka - Ainia, Qurrotul (Maliki Interdisciplinary Journal, 2025)
Changes in the curriculum are one of the ways the national education system adapts to the demands of the times and the progress of society. One significant change is the implementation of the Merdeka Curriculum, which began in 2022 by the Ministry of Education, Culture, Research, and Technology. This curriculum emphasizes flexibility, student-centered learning, and strengthening the character of Pancasila students through project-based activities. However, the implementation of the Merdeka Curriculum presents its own challenges for Islamic educational institutions such as madrasahs and pesantren, which have distinctive characteristics, visions, and unique learning methods. This study examines how strategic management is used by Islamic educational institutions in responding to these changes, as well as how SWOT analysis is applied to design adaptive strategies in implementing the Merdeka Curriculum. The findings indicate that strategic management plays an important role for Islamic educational institutions in establishing their vision, developing adaptive policies, and adjusting the curriculum without compromising Islamic values. With the help of SWOT analysis, madrasahs and pesantren can identify their strengths, weaknesses, opportunities, and threats, enabling the implementation strategy of the Merdeka Curriculum to become more adaptive and sustainable.